2020
DOI: 10.15294/jllr.v1i3.38090
|View full text |Cite
|
Sign up to set email alerts
|

Dynasty Politics in Indonesia: Tradition or Democracy?

Abstract: The presence of political dynasties that encompassed power struggles at regional to national levels resulted in the substance of democracy itself being difficult to realize. The flourishing of political dynasties - especially in the regions - is inseparable from the role of political parties and regulations on the elections. Oligarchy in the body of political parties causes the mechanism of candidacy and nomination to not run as it should. During this time, there is a tendency for candidates to be nominated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 1 publication
0
11
0
1
Order By: Relevance
“…The theory (Mukti & Rodiyah, 2020) states that political dynasties are a tradition in Indonesia and can be proven with the historical record of the previous president who secured his descendants' power position before retirement (Suryatwan, 2020) Jokowi also did the same. Not only that, but the practice of oligarchy in Indonesia is very transparent, and there is no longer any impression of being covered up.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The theory (Mukti & Rodiyah, 2020) states that political dynasties are a tradition in Indonesia and can be proven with the historical record of the previous president who secured his descendants' power position before retirement (Suryatwan, 2020) Jokowi also did the same. Not only that, but the practice of oligarchy in Indonesia is very transparent, and there is no longer any impression of being covered up.…”
Section: Discussionmentioning
confidence: 97%
“…Apart from that, the community is also concerned about leading the region. Previously, they were deemed not to have the ability and sufficient political footprint, so that the public only considered them to take advantage of the political momentum by completing the President's reputation and position.Furthermore, according to (Mukti & Rodiyah, 2020), The practice of political dynasties in real democracy does not exist. In the constitution, every citizen's rights are guaranteed and upheld to vote and be elected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Riewanto's research (2020) show that there is a correlation between political dynasties in Simultaneous Pilkada and corrupt practices. Various studies (Mukti and Rodiyah, 2020;Arianto, 2021;Rahmatunissa, 2021;Dedi, 2022) found that the politics of kinship in Pilkada has damaged the quality of democracy at the local level. The research of Setyaningrum and Saragih (2019) show that political dynasties negatively affect local government performance.…”
Section: Unnes Journalsmentioning
confidence: 99%
“…The power of the ancestors (papa se tete, kapita and momole) becomes a strength, optimism and militancy that must live in an elite and political actor so that the model of the long rituals is to maintain mental and strength in the political struggle (Mukti and Rodiyah, R. (2020)). Indonesian politics is part of the dimensions of custom and tradition as it is a human entity of the archipelago.…”
Section: Cultural Relation and The Strategy Of Clans Mobilization In ...mentioning
confidence: 99%